Anion-exchange extraction of mefenamic acid - Gulevich, Alyaksandr L.; Rakhman’ko, Evgenii M.; Egorov, Vladimir V.; Smirnova, Marina S. (Journal of the Belarusian State University. Chemistry, 2019)
Anion-exchange extraction of mefenate anions with toluene solutions of trinonyloctadecylammonium picrate was studied. It has been established that the introduction of solvents with acid properties – chloroform and n-octylalcohol – into the organic phase leads to a sharp increase in the concentration exchange constants. The greatest effect was observed when trifluoroacetyl solvating additives were introduced into the organic phase. The corresponding solvation constants and average solvate numbers are calculated. A simple and selective extraction-photometric method for the quantitative determination of mefenamic acid in the drug «Mefenamic acid-Darnitsa» has been developed.
Keywords: anion-exchange extraction; high-molecular quaternary ammonium salts; mefenamic acid; trifluoroacetyl solvating agent